2019
DOI: 10.1088/1612-202x/aafd1e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the nonlocal advantage of quantum coherence by local parity-time (PT)-symmetric operation

Abstract: In this letter, we explore the dynamics and protection of nonlocal advantage of quantum coherence (NAQC) for an entangled two-qubit system subjected to a noisy environment by performing parity-time (PT) symmetric operations on one of the two particles. For comparison, we investigate the protection of Bell nonlocality, quantum coherence, and entanglement by local PT-symmetric operations. Here, we show that the NAQC, Bell nonlocality, quantum coherence, and entanglement of a bipartite entangled state can be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…In [26] the authors found that the no-signaling principle can be violated when applying a local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of an amplitude damping (AD) model [27][28][29][30][31] and slow down the decoherence of the pure phase damping model [32], and so on. Moreover, recent research [33] has shown that the qubit-qubit entanglement can obviously be enhanced by means of either local, prior, or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%
“…In [26] the authors found that the no-signaling principle can be violated when applying a local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of an amplitude damping (AD) model [27][28][29][30][31] and slow down the decoherence of the pure phase damping model [32], and so on. Moreover, recent research [33] has shown that the qubit-qubit entanglement can obviously be enhanced by means of either local, prior, or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%
“…In [13] the authors found that the no-signalling principle can be violated when applying the local PT -symmetric operation on one of the entangled particles. More recently, it has also been shown that PT -symmetric operation can be used to suppress the decoherence of amplitude damping model [14][15][16][17][18][19][20][21], and slow down the decoherence of the pure phase damping model [22].…”
Section: Introductionmentioning
confidence: 99%
“…In [31], the authors found that the no-signalling principle can be violated when applying the local non-Hermitian operation on one of the entangled particles. More recently, it has also been shown that non-Hermitian operation can be used to suppress the decoherence of amplitude damping model [32][33][34][35][36], and slow down the decoherence of pure phase damping model [37], and so on. Moreover, recent research [38] has shown that the qubit-qubit entanglement can obviously be enhanced by the means of either local prior or post non-Hermitian operations.…”
Section: Introductionmentioning
confidence: 99%